2014
DOI: 10.3747/co.21.1984
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chemotherapy-Induced Neurotoxicity on Psychological Distress and Sleep Sisturbance in Cancer Patients

Abstract: quality in cancer patients treated with chemotherapy. High pnq grades were significantly associated with poor psychological status and sleep quality. Our results emphasize the importance of assessing peripheral neuropathies during chemotherapy and of adjusting treatment plans based on assessment results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 52 publications
5
54
1
2
Order By: Relevance
“…A cross-sectional study has evaluated 706 patients with regard to the influence of CIPN in the development of mental and sleep disorders after the fourth week of potentially neurotoxic anticancer treatment. The worst CIPN severity, the highest the frequency of anxiety, depression and sleep disorders, which were worsened by neuropathic pain 24 . Cognitive impairment, non-adherence to treatment and loss of self-care ability are also described.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study has evaluated 706 patients with regard to the influence of CIPN in the development of mental and sleep disorders after the fourth week of potentially neurotoxic anticancer treatment. The worst CIPN severity, the highest the frequency of anxiety, depression and sleep disorders, which were worsened by neuropathic pain 24 . Cognitive impairment, non-adherence to treatment and loss of self-care ability are also described.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Verbalization of frustration feelings is common as a consequence of social role impairment, of distress due to functional skills changes, in addition to dismay and loss of objectives due to the need to give up some activities 24 . A study has investigated 240 females with breast cancer and CIPN, observing frequent reports of difficulties to drive, to notice texture and temperature differences, to walk on high heels, to button a blouse, to comb their hair or even to cook 23 .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The effect of chemotherapy on sleep quality has been well documented in patients with cancer (Bischel et al, ; Hong et al, ). Palesh et al () concluded that the rate of sleep disturbance was three times higher in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the standard chemotherapeutic agents for OS may generate many adverse short-term and long-term health impacts (Longhi, Ferrari, Bacci, & Specchia, 2007). In previous studies, sleep disturbance has been reported as a side effect of chemotherapy in patients with cancer (Bischel et al, 2016;Hong, Tian, & Wu, 2014). Specifically, paediatric cancer patients treated with chemotherapy may be more vulnerable to increased cluster of fatigue and sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The health impacts of CIPN remain worrying because CIPN is associated with comorbidities such as psychological distress. 15 However, these long-term effects remain poorly studied. The degree of neurotoxicity depends on the type and combination of drugs used, the duration of administration, and the cumulative dose applied.…”
Section: Discussionmentioning
confidence: 99%